Possibilities of keystroke dynamics analysis for early stress recognition in office environment - Rahmouni, A. (ХНУРЕ, 2023)
This thesis explores the possibilities of keystroke dynamics analysis as a method for early stress recognition in office environments. Chronic stress in the workplace is a growing concern, with negative consequences for both employees and organizations. Traditional methods of stress detection have limitations in terms of accuracy and practicality, and there is a need for alternative approaches. Keystroke dynamics analysis, which involves analyzing typing patterns, has shown promise as a non-invasive, unobtrusive, and cost-effective tool for stress detection. The aim of this thesis is to investigate the potential of keystroke dynamics analysis as a stress detection method, including its advantages and limitations, and its application in real-world office settings.
Keywords: Delay time; digraph; keystroke dynamics; office worker; trigraph